Auxin type and dilution vehicles on vegetative propagation of Varronia curassavica Jacq. and Melaleuca alternifolia Cheel - Pereira, Marcelo; Gonçalves, Lilian Fernanda Sfendrych; Gomes, Erik Nunes; Rossa, Überson Boaretto; Deschamps, Cícero (Ornamental Horticulture, 2021)
Studies on the propagation of medicinal and ornamental plant species show of great relevance as they contribute to the domestication, cultivation and production of these species. However, there are not enough information concerning the interaction of the different plant growth regulators and the recommended dilution vehicles. This work aimed to evaluate the effects of sodium hydroxide (NaOH) and ethanol as rooting inducers, as well as their performance as vehicles for diluting indolebutyric acid (IBA) and naphthalene acetic acid (NAA) in stem cuttings of the species Varronia curassavica and Melaleuca alternifolia. Stem cuttings of both species were submitted to the treatments: control with distilled water, hydroethanolic solution (50% v v-1), NaOH solution in distilled water, indolebutyric acid diluted in hydroethanolic solution, indolebutyric acid diluted in NaOH solution, naphthalene acetic acid diluted in hydroethanolic acid and naphthalene acetic acid diluted in NaOH solution (0.5 N). The design used was completely randomized, with the averages compared by the Scott-Knott test at 5% probability. Better rooting of the cuttings was observed when IBA was applied using both dilution vehicles. For M. alternifolia, percentages of average survival of 26.43% were verified. Rooting was more satisfactory when using NaOH as a dilution vehicle for both IBA (16.66%) and NAA (23.33%). For V. curassavica, IBA (2000 mg L-1) is the most suitable plant regulator, diluted in both hydroethanolic solution and in NaOH, while for M. alternifolia, NaOH is recommended as a dilution vehicle for plant growth regulators NAA (500 mg L-1) and IBA (500 mg L-1). When applied isolated, the dilution vehicles do not stimulate and do not harm the rooting of the two species.